2021
DOI: 10.3390/ma14216698
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Determination of Droplet and Nanoparticle Size Distributions in Spray Flame Synthesis by Wide-Angle Light Scattering (WALS)

Abstract: The investigation of droplet and nanoparticle formation in spray flame synthesis requires sophisticated measurement techniques, as often both are present simultaneously. Here, wide-angle light scattering (WALS) was applied to determine droplet and nanoparticle size distributions in spray flames from a standardized liquid-fed burner setup. Solvents of pure ethanol and a mixture of ethanol and titanium isopropoxide, incepting nanoparticle synthesis, were investigated. A novel method for the evaluation of scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…However, only measurement techniques based on electron microscopy or light/X-ray scattering provide the necessary information [ 17 ]. Here, wide-angle light scattering (WALS) has shown great potential to analyze the shape and size of aggregates in the micrometer range [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, only measurement techniques based on electron microscopy or light/X-ray scattering provide the necessary information [ 17 ]. Here, wide-angle light scattering (WALS) has shown great potential to analyze the shape and size of aggregates in the micrometer range [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Species detected, e.g., by LIF, include Fe, FeO, SiO, AlO, TiO, and others . Laser methods can be difficult to apply in dense media with spray and particle clouds, but techniques such as LII, LIBS, and line-of-sight attenuation can be valuable for analyzing the process development and/or materials properties in situ . ,,,, Further diagnostic approaches include tomographic imaging with multiple simultaneous emission measurements, wide-angle light scattering for in situ determination of droplet and particle size distributions, and mass spectrometry to probe the particle growth. , To improve the understanding of flame synthesis reaction systems further, specific aspects have been investigated in depth, for example by studying atomization, droplet formation, and droplet–gas phase interactions, or by modeling the dynamics of SiO 2 nanoparticle synthesis using Reynolds-averaged Navier–Stokes (RANS) or large eddy simulation (LES). , …”
Section: Developments For Systems and Applicationsmentioning
confidence: 99%
“…Yang et al [ 159 ] observed the isolated titania particles in the high-temperature region, and a sintering equation was developed based on the light scattering data. Simon et al investigated the size distribution of TiO 2 nanoparticles using a wide-angle light scattering method with pulsed light at 532 nm, which could also identify the presence of morphological fraction [ 170 ]. The formation of silica particles in co-annular diffusion flame was investigated by Adrian et al [ 160 ] using an in situ small-angle X-ray scattering (SAXS) technique, with the ability to monitor the mass fractal dimension, aggregate size, and the number of primary particles per aggregate.…”
Section: Measurement Techniquesmentioning
confidence: 99%